Human Freedom and the 'Reality of Society': Origins and Development of Karl Polanyi's Ideas during the Interwar Period - Thomasberger, Claus (History of Economic Thought, 2005)
Karl Polanyi's most famous book, The Great Transformation, contains several ideas and theoretical notions which are at the heart of long-lasting controversies throughout the social sciences. Categories such as "double movement," "embeddedness," "disembedding," "market society," or "social freedom" have proved to be fruitful notions not only in anthropology, but also in sociology, political sciences, and economic history. The recent three volume publication of Karl Polanyi's writings during the interwar period–including published articles and unpublished manuscripts–opens for the first time the possibility to have a closer look at the origins and the development of some of Polanyi's concepts during the interwar period. In the paper titled "Human Freedom and the Reality of Society–Origins and Development of Karl Polanyi's Ideas during the Interwar Period," Claus Thomasberger addresses Polanyi's idea of a polar relationship between human freedom and the "reality of society." The paper offers new insights, discussing central questions which are crucial to the understanding of Polanyi's reasoning: Where are the roots of his central categories? What influence did Marx have on Polanyi's thinking? What is the relationship between Polanyi's approach and the Austrian School of Economics? Is it appropriate to read his work in terms of an institutional approach? In order to give an answer to these questions, the paper goes back not only to the 1930s, but to the 1920s as well. As it demonstrates, Polanyi had already developed the core ideas of his thinking in Vienna, participating actively in the discussions between the Austrian School of Economics and Austro-Marxism about the possibilities of a socialist society.
Economics; Philosophy
Keywords: history of economic thought: individuals; reality of society

Two heterodox economists: Neurath and Karl Polanyi - Giandomenica, Becchio (MyScienceWork Working paper No. 11/2005 Università di Torino 1, 2005)
This paper is based on the idea that between the 1920s and the mid-1930s in Vienna there were two forms of heterodox economic theory: the Austrian economic school headed by Ludwig von Mises and another interesting form of heterodox economics opposed to the Austrian school (above all politically) and pursued by various social thinkers (Otto Neurath, Karl Polanyi, Otto Bauer, Felix Schaffer, Felix Weil, Jacob Marschak). They were engaged in the debate on the possibilities of a planned economy: Austrian socialist economists proposed a sort of ‘third’ way between pure capitalism (whose Viennese stronghold was the Austrian economic school) and orthodox communism à la Kautzsky (deeply rooted in Germany). This paper focuses on the affinities between Neurath and Polanyi’s economic thought: despite some major differences between them, they shared a common philosophical background on which they founded their heterodox economic theory. After a brief historical premise, there is a first part, which deals with the debate on a planned economy and a second part, which deals with the influence of Neurath on the Polanyi’s vision of the faults of the neoclassical economic theory: the concepts of “disembedded economy” and of the so-called “economicistic fallacy”. NEURATH AND POLANYI IN VIENNA Neurath described himself as a ‘social engin
Economics; Philosophy
Keywords: Austrian economic school; NEURATH; Otto; economics; heterodox economics; philosophy; political science